Kitchen exhaust ventilation: promotion of the establishment on the integrated sustainable industry at R&D Halton Group Sdn. Bhd. - Asmuin, Norzelawati; Alimin, Ahmad Jais; Salleh, Hamidon; Ismail, Al-Emran; Mohd Ali, Mas Fawzi; Mat Isa, Norasikin; Manshoor, Bukhari; Sadikin, Azmahani (Penerbit UTHM, 2020)
Halton Group is an international company specializes in indoor climate and indoor environmental products, services and solutions. Halton's aim is to create comfortable and safe indoor environments that have energy-efficient and sustainable life cycle. Halton Group Asia Sdn, Bhd, is the company’s branch in Malaysia. Recently, Halton Group Asia establishes their R & D division which focus on the design and development of kitchen exhaust ventilation for worldwide hotels and restaurants. Halton Group has long been working closely with Universities around the world to assist their R & D division. In Malaysia, the company has entrusted Centre for Energy and Industrial Environmental Study (CEIES), UTHM, to provide the expertise to enhance the efficiency of their system especially in improving the quality of kitchen exhaust ventilation treatment.